Caracterização de um modelo de osteoartrite induzida pela anteriorização cirúrgica do disco articular em ratos - Togni, Lênio (2017)
Objective: This study aimed to characterize the development of temporomandibular osteoarthritis (TMJ-OA) following the surgical anterior displacement of the articular disc (ADD) in rats, in comparison to the well-established model of OA induced by the intra-articular injection of the inflammatory agent CFA. Methods: Male Wistar rats (160-180 g) were randomly divided into two surgical groups, namely ADD (submitted to anterior disc displacement) and sham-operated (surgical access, without ADD). For purposes of comparison, two additional experimental groups received an intra-articular infiltration of complete Freund’s adjuvant (CFA; 50 μl/site; 1:1 oil/saline emulsion), or the same volume of saline solution (0.9% NaCl). Different experimental subgroups (N=8 per group) were euthanized on 15, 30 or 60 days after procedures. The region corresponding to the left TMJ was collected for histological analysis of fibrocartilage thickness (hematoxylin-eosin staining), presence of proteoglycans (safranin-O and toluidine blue), subchondral bone metabolism (tartrate-resistant acid phosphatase; TRAP) and collagen levels (Masson's trichrome). The immunopositivity for the aggrecanase ADAMTS5 was examined in the fibrocartilage layers. Micro-CT images were acquired for morphological and microstructural evaluation (30 and 60 days; N=4 per group). The levels of inflammatory serum proteins (IL-1ß, IL-6 and TNF) were assessed to evaluate the possible systemic outcomes of TMJ-OA induced by ADD or CFA. Results: The analysis of hematoxylin-eosin-stained sections revealed an increment of fibrocartilage thickness in the ADD group, on 15 and 30 days, mainly in the anterior third of the condyle. In the CFA group, a fibrocartilage thickening was seen in the posterior third, only at 15 days. Increased proteoglycan contents were present in the fibrocartilage of the ADD group, according to the qualitative analysis by safranin-O and toluidine blue staining. The ADD group also displayed an augmented immunopositivity for ADAMTS5 in the fibrocartilage cells, on 15 and 30 days, whereas the expression of this aggrecanase was subtly increased in the CFA group at 15 days. The histological evaluation of the subchondral bone did not reveal any evident difference in the collagen contents, or in the number of activated osteoclasts, in the ADD or CFA groups, as indicated by Masson’s trichrome and TRAP staining. However, the micro-CT analysis showed marked morphological and structural changes in condyles of the ADD group, with osteophyte formation on 30 days, and a flattening of condylar surface on 60 days. The anterior condyle third of the ADD group also presented an increment of trabecular separation and bone surface, associated to a reduction of trabecular thickness and bone volume. The serum levels of the pro-inflammatory cytokines, namely IL-1ß, TNF or IL-6, were undetectable in all the experimental groups. Conclusion: The surgical model of ADD in rats led to long-term OA-like alterations, with the formation of osteophytes, followed by flattening of the condyle surface and trabecular derangements. This experimental model might represent a reliable strategy to investigate TMJ-OA-related mechanisms, allowing the identification of novel therapies for this condition.